CT and MR findings in patients with chordomas of the petrous apex. - Brown, R V; Sage, M R; Brophy, B P (American Journal of Neuroradiology, 1990)
Chordomas are rare neoplasms arising from remnants of the embryologic notochord. Although typically midline in site, intracranial tumors may arise off the midline, and a significant proportion of these arise unilaterally in the petrous bone. Three examples of this entity are presented, all demonstrating typical radiologic features. Dendritic branches of the cranial end of the notochord ramifying in the skull base are thought to provide the embryologic basis for this tumor. The CT and MR features demonstrated are similar to those of the more common midline chordomas. CT demonstrates a well-defined extraaxial soft-tissue mass associated with foci of calcification and bone destruction and occurring at a site corresponding with the embryologic distribution of notochordal material. On MR, prolonged T1 and T2 relaxation times result in hypointensity on T1-weighted images and marked hyperintensity on T2-weighted images. Signal voids result from the foci of calcification while hemorrhage may also lead to inhomogeneity.